DESAIN SISTEM INFORMASI PENGELOLAAN PERIKANAN BERBASIS WEB (Information Technology and Telematics, 2013)
The purpose of this study is to analyze the data and existing systems and improve it so that it can presentthe information accurately and appropriately in entering data and Memepercepat catches the fishermen.Analysis of the new planning system in fisheries management information system at the Department of Marine and Fisheries Semarang includes an evaluation of the proposed system, Data Flow Diagrams (DFD) and Entity Relationship Diagram (ERD), database specifications, process design and implementation plan.Based on the analysis and research on the author, it can be concluded that in the old system, in making data report catches desperately need a relatively long time, so that in the presentation of the information is often ineffective and inefficient. This result lead to burnout, fatigue, as well as complaints from the officers, resulting in the accumulation and delay the work. The new information system with computerized application of expected information provided accurate and timely.Keywords: Fisheries Management Information Systems, PHP, MySQL, Capture fisheries.